Вы находитесь на странице: 1из 9

3

3.
.
.
. . 56

.-. . 231
. . 34
, .
:

A+BD
r = - d[B]/dt = k [A] [B]

(1)

,
.

A + C F.
r = - d[C]/dt = k [A] [C]

(2)

- (1)
.
,
.
.
.
. . 58-60

.-. . 256-257
. . 41-43
:

A B;

AC

r = - d[A]/dt = kb [A] + kc [A] = (kb + kc) [A]

(3)
1

3
(3):

ln[A]/[A0] = - (kb + kc) t

(4)

ln[A]/[A0] = f (t)
.
, :

d[B]/dt = kb [A]; d[C]/dt = kc [A]

(5)

, , :

d[B]/dt = kb [A] = kb [A0] e


t

( k B + kC ) t

; d[B] = kb [A0] e

dt

kb
* e ( kb + kc ) t *[ A0 ]
kb + k c
0
0
( k + k )t
[B] [B0] = -{kb / (kb + kc)} [A0] { e B C 1}
[ B] =

( k B + kC ) t

(6)

[] [0] = -{k / (kb + kc)} [A0] { e

( k B + kC ) t

1}

(7)

[ B] [ B0 ] kb

=
[
C
]

[
C
]
kc
0

kb
kb
[ B ] = *[C ] + [ B0 ] [C0 ]*
kc
kc

[B] = f[] (kb


:

(8)
/kc)}

A+DB
A+
:

- d[D]/dt = kb [A] [D];

- d[]/dt = k [A] []

d[D] /d[] = kb / kc {[D]/[]}

(9)

ln [D] ln [D0] = kb / kc {ln []} - kb / kc {ln [0]}


ln [D] = f{ln
.

(10)

[C]}

(9) , ,
.
.
. . 57-58

.-. . 199-201
. . 34-37
, .
- :

A=B
:

r = - d[A]/dt = k1 [A] - k-1 [B]

(11)

[B] = [A0] - [A] + [B0]


- d[A]/dt = {k1 + k-1} [A] k-1 {[A0] + [B0]}

(12)

L=

k1
* ([ A0 ] + [ B0 ])
( k1 + k1 )

(13)

d [ A]
= (k1 + k1 ) * ([ A] L )
dt

(14)

d [ A]
= (k1 + k1 ) * dt
([ A] L )

(15)

0 t:

ln{[A] L} = - {k1 + k-1}t + ln {[A0] L}

{[A] L} = {[A0] L}* e

( k1 + k1 ) t

(16)

t . (16)
, :

[A] - L = 0
[A] =L =

k1
* ([ A0 ] + [ B0 ])
k1 + k1

(17)

[A0] + [B0] = [A] + [B]


[B] = [A0] + [B0] - [A]

(18)

[ B ] = ([ A0 ] + [ B0 ]) [ A ] =

([ A0 ] + [ B0 ])

k1
* ([ A0 ] + [ B0 ]) =
( k1 + k1 )

([ A0 ] + [ B0 ]) * 1

k1
=
( k1 + k1 )

(19)

k1
A
B
[
]
[
]
*
+
( 0
0 )
( k + k )
1 1

:
[A] / [B] = k-1/ k1 = 1/K

(20)

3
ln{[A]

L} = ln{[A] [A]} = f (t)

, .
,
,

L=

k1
1
* ([ A0 ] + [ B0 ]) =
* ([ A0 ] + [ B0 ])
k
k
1
K
+
+
( 1 1 )

, , L.

ln{[A] L} = f (t) ( (14)) ,


!
.
(
!) ( !)

K=

aB B [ B ] k1
=

a A A [ A] k1

, ,

) ;

) , ,
, . ,
.
.

k -1 [B]
r = r1 - r-1 = k1 [A] - k-1 [B] = k1[A]* 1

k
[A]

(21)

G = - Ac = B - A

(22)

A = A0 + RT ln [A];

{B0 - A0} = G0 = - RT ln K
7

- Ac = B - A = {B0 - A0} + RT ln

[B]
[B]
= -RT ln K + RT ln
(23)
[A]
[A]

- , :

[ B]
[ B]
AC
= ln
= ln

RT
[ A]* k1
[ A]* K

k1

A =

r
e RT = 1
r1

r
= ln 1

r1

(24)

(25)

r = r1 r1 = r1 * (1 e

A =
RT

) = k1 *[ A]* (1 e

A =
RT

(26)

(26) , , (
!), . (26)
. , ..
(
) .
,

G
= G = = A = < 0

T , p
G


=

G
=

A
=
=

<0

T , p
T , p
T , p

(27)


( !). (27)
, . (27)
.
8

3
,

( G )T , p = G = (1)d (1) + G = (2)d (2) < 0


G
d (1)
d (2)
=

<0
G
G
(1)
(2)

=
=
dt
dt
t T , p

(28)

(28) , ,

d (1) d (2)
>0
;
dt
dt
G = (1) < 0, G = (2) > 0

(29)

.
.
(2) ,
, (28) (29).
.
1) ,
, .. ;
2)
( !).
, .. .
3)
(28), (29) .. , .

Оценить